PENGARUH PENGGUNAAN APLIKASI PHET TERHADAP PENINGKATAN HASIL BELAJAR SISWA KELAS IV DALAM PEMBELAJARAN IPA - Alya, Mughni; Sari, Siti Mayang; Zahraini (Universitas Veteran Bangun Nusantara, 2025)
Education in Indonesia, especially at the elementary school level, plays a very important role in forming the foundation of knowledge and skills that students will use throughout their lives. Therefore, it is important to develop innovative learning methods to improve student understanding. This study aims to examine the effect of using the PhET application on improving the learning outcomes of fourth-grade students of SDN 14 Banda Aceh in science learning. The method used in this study was an experiment with a pretest-posttest control group design. The results showed that the PhET application can significantly improve student learning outcomes. The experimental group showed a greater increase than the control group. The average posttest score of students in the experimental group increased significantly, this shows that the PhET application in science learning in elementary schools can help students understand difficult science concepts so that it can improve student learning outcomes. Based on the results of the study, it can be concluded that through the PhET application, student learning outcomes can be improved by 92% in science learning for fourth-grade students of SDN 14 Banda Aceh. The use of technology in science learning can have a positive impact on increasing student involvement and student understanding of the material being taught